Generations of Warfare and the Future of the Hybrid Wars - Artsrun Hovhannisyan (Banber Arevelagitut'yan Instituti, 2025)
The article is about the generations of war and expounds on Hybrid wars. Its connection to the model of generational divisions is detailed. Today, as well, with the Cold War is over, the hyperactivity of the US in the military-political arena has brought forth a similar storm. The American war machine is in a victory march. At the same time a variety of ideas and theories of war are brought forth and being discussed. There are differing views on how generations of war should be classified. In my opinion, the main spheres of human development, such as that of commerce, economics, politics, science, education and culture, are the main determining factors. Taking into consideration the various factors, wars have been divided into the following six generations. Fifth generation warfare's necessity became apparent during fourth generation wars. The main elements in question were automated control systems and precision-guided armament. Along with new political, economic and social developments, these ensured new victories. Again, in this generation, armies chose to avoid operations that required large scale mobilization, and instead tried promptly sending small groups into battle, avoiding large-scale preparatio. The issues in the fields of war, as well as the issue of waves of communication, reached their peak. This generation, once and for all, confirmed the importance of force accumulation on any platform, anywhere in the world. Fifth generation wars brought armies to a point where they retired from classical combined arms warfare; Electro- Fire Battle is more commonly applied. Trenches and engineered structures are nearly extinct. This was yet another example of believing in the superiority of quality over quantity. The effects of information became a decisive factor. These were the wars of the digital media industry.